BIAYA KUALITAS, PRODUKTIVITAS DAN KUALITAS PRODUK : SEBUAH KAJIAN LITERATUR - Lores, Linda; Siregar, Retnawati (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2019)
This study aims to examine the types of quality costs and their relationship with product productivity and quality in the companies. This research is a conceptual literature. Quality defines as customer satisfaction while productivity is the ratio between the outputs produced. This study shows the quality costs are directly related and have an impact on productivity, and product quality. Types of quality costs that are closely related to productivity and product quality are costs that arise with control activities including prevention and valuation costs. Cost of quality can produce high quality products ranging from increased productivity to the product will be produced and customer satisfaction is created. The cost of failure is inversely proportional to the cost of prevention and evaluation of quality and productivity. Companies can do this by reducing quality costs and improving quality for their customers with the most commonly applied methods with a classic prevention-assessment-failure (P-A-F) model or with other concepts and utilizing information technology.